On a Hall Hypothesis - Tyutyanov, V. N.; Тютянов, В. Н.; Тютянов, В. Н. (Institute of Mathematics, NAS of Ukraine, 2002)
We obtain a new criterion for the solvability of a finite group with a given family of Hall subgroups.